The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1159/000091059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irradiation on in situ Remineralization of Human and Bovine Enamel Demineralized in vitro

Abstract: The objective of this study was to evaluate the effects of irradiation and surface condition on in situ remineralization of demineralized human and bovine enamel. Specimens (n = 96) obtained from 24 human molars and 24 bovine incisors were prepared. The surfaces of half of the specimens were abraded while the others remained natural. Each of the 12 human and bovine abraded and sound specimens was irradiated fractionally up to 46.5 Gy (3.1 Gy/day, 5 days/week), while the remaining samples were not irradiated. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 40 publications
3
45
0
4
Order By: Relevance
“…Therefore, 68 papers were included in the final review. The studies covered seven main categories: morphology (5 studies) (22)(23)(24)(25)(26), chemical composition (11 studies) (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), physical properties (12 studies) (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), dental caries (7 studies) (6,9,(50)(51)(52)(53)(54), dental erosion/abrasion (10 studies) (55)(56)(57)(58)(59)(60)(61)(62)(63)(64), bonding/adhesive strength (17 studies) (65)(66)(67)(68)…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 68 papers were included in the final review. The studies covered seven main categories: morphology (5 studies) (22)(23)(24)(25)(26), chemical composition (11 studies) (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), physical properties (12 studies) (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), dental caries (7 studies) (6,9,(50)(51)(52)(53)(54), dental erosion/abrasion (10 studies) (55)(56)(57)(58)(59)(60)(61)(62)(63)(64), bonding/adhesive strength (17 studies) (65)(66)(67)(68)…”
Section: Search Resultsmentioning
confidence: 99%
“…Dental caries studies Table 1 shows the details of the seven studies reviewed (6,9,(50)(51)(52)(53)(54). There were four in vitro studies (6,9,50,51), one in situ study (52), and two in vitro/in situ studies (53,54).…”
Section: In Vitro Permanent Enamel Crown Nanoindentation Profilometrymentioning
confidence: 99%
“…16,17,24,25,26,27 However, only limited information is available concerning these effects on both enamel and dentine. Moreover, most of the previous investigations had limitations with regard to the instruments used, and there has been little study concerning the relationship between radiation dose and mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…2,12,13 However, in recent years, some scientists have suggested that direct radiation damage can ratchet up the progression of radiation caries; in their studies, morphological and physical changes in both human and bovine dentine were documented after radiotherapy. 14,15,16,17 Unfortunately, the explanation regarding changes in the nano-mechanical properties of teeth has generated controversy in dental literature, and no in vivo study has reported the crucial radiotherapy dose-time relationship regarding the prevention of radiation caries. In vitro studies have limitations with regard to clinical conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…No experimento in vitro foi observada diferença significativa entre os No estudo in situ, a radiação gama, para esterilização das amostras de esmalte utilizadas no dispositivo, não interferiu na diminuição da desmineralização ou na ativação da remineralização, como prevê a literatura [Kielbassa et al, 2006] Desta maneira, a maior adsorção causa um efeito prolongado da aplicação profissional (FFA + laser), em ambiente clínico. O uso de dentifrício, em ambiente doméstico, mantém o contínuo aporte de fluoreto para a formação de produtos de superfície de esmalte, solicitados nos ciclos de pH.…”
Section: 11-análise Morfológica Por Microscopia Eletrônica De Varrunclassified